2016
DOI: 10.1007/s11748-016-0647-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of atrial fibrillation and inflammatory response after on-pump coronary artery bypass using different statin dosages: a randomized, controlled trial

Abstract: European Clinical Trials Database (EudraCT: 2006-005757-30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The incidence and mortality of ARDS in patients undergoing CPB were reported to be 0.4% to 0.6% and 15% to 41.5%, respectively. 2,3 Although various methods have been proposed to protect organs from impaired situations, such as leukocyte-depleting filters 4 ; monoclonal anticytokine antibodies 5 ; and pharmacologic manipulations by corticosteroids, polymorphonuclear elastase inhibitors, or statins, 6 only a few modalities are currently used in practice.…”
Section: See Editorial Commentary Page 1984mentioning
confidence: 99%
“…The incidence and mortality of ARDS in patients undergoing CPB were reported to be 0.4% to 0.6% and 15% to 41.5%, respectively. 2,3 Although various methods have been proposed to protect organs from impaired situations, such as leukocyte-depleting filters 4 ; monoclonal anticytokine antibodies 5 ; and pharmacologic manipulations by corticosteroids, polymorphonuclear elastase inhibitors, or statins, 6 only a few modalities are currently used in practice.…”
Section: See Editorial Commentary Page 1984mentioning
confidence: 99%
“…The authors allowed subjects to begin rosuvastatin therapy from 2 up to 8 days prior to surgery, whereas the ARMYDA trial began all subjects on atorvastatin at 7 days preoperatively. Another recent study by Pierri et al which showed a dose dependent trend toward lower postoperative AF for perioperative atorvatatin with on-pump CABG, also used 7 days of statin therapy prior to surgery (8). Based on the results of these studies, we speculate that at least 1 week of pre-operative statin therapy may be needed to achieve benefit.…”
mentioning
confidence: 74%
“…Ultimately, future studies should address the role of statin therapy in patients undergoing cardiac valve surgery to reduce postoperative AF because these patients may have a higher prevalence of statin naïve patients. A randomized controlled trial with this model could address statin versus placebo, as well as a head-to-head comparison of atorvastatin and rosuvastatin in terms of postoperative AF rates because trials with atorvastatin suggest a benefit of perioperative statin therapy (3,8). A trial of this nature could help address whether statin initiation at the time of preoperative planning is indicated and whether there is any real difference in outcomes between atorvastatin and rosuvastatin.…”
Section: Editorialmentioning
confidence: 99%
“…The risk of new-onset AF was decreased by statin use within 1 month after discharge in patients with myocardial infarction or coronary revascularization [ 27 ]. According to Pierri et al, 7-day preoperative treatment with statin decreased the incidence of AF after surgery [ 28 ]. Recent evidence showed that statins can decrease the risk of stroke proportional to the degree of cholesterol reduction by lowering TC and LDL-C [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%